Investigation of the relationship between in vitro vitamine and antioxidant activites of rose species collected from same ecological conditions - Fatma ERGÜN; Mustafa YAGCI (Journal of Animal and Plant Sciences, 2024)
Understanding the chemical potentials of the fruits of rosa species initially used for food and curing of diseases, led to an increase in the amount of consumption and the variety of use over time. In order to determine the usage possibilities of these fruits, which have a wide variety of chemical properties, it is necessary to know the properties such as antioxidant activity, the amount of vitamins, phenolic and flavonoid substances and the differences within rose species. In this study, naturally grown in the same ecological environment, the fruits of Rosa villosa L. subsp. mollis (R1), Rosa villosa L. subp. villosa L. (R2), Rosa pimpinellifolia (R3), Rosa iberica (R4), Rosa pisiformis (R5) and Rosa canina (R6) were investigated with respect to their vitamin values ??(A, E and C vitamins), total phenolic (TPC) and flavonoid (TFC) content, and antioxidant potentials with the correlation ratios between these determined properties. The showed that the highest amount of TPC and TFC were 142.08±2.16 mgGAE/g, 8.04±0.47 mgQE/g, respectively in R1, and the highest vitamin values ??were determined, vitamin A at 397.17±13.58 µg/mL in R5, Vitamin E at 19.52±0.82 µg/mL in R4 and vitamin C at 606.53±0.38 µg/mL in R1. DPPH, FRAP, CUPRAC methods, which are reliable methods, were used to determine the antioxidant potential. The highest antioxidant potential was measured at R1 by DPPH and FRAP methods. In R3, it was found that the Cu2+ reduction antioxidant activity was the highest with the CUPRAC method. In addition, it was understood that the correlation analysis among the determined characteristics of the species was statistically significant, there was a high positive correlation between TFC and vitamin E value in R1 and between TPC and E in R2. As a result, although significant quantitative differences were detected between Roseship species in this study, it was determined that the antioxidant potentials and vitamin values ??of all species were high. The results showed that the important the fruits of these species would be used for our nutrition and health. Among the species, especially Rosa villosa L. subsp. mollis (R1) was more suitable for using fort he purposes of pharmaceutical, functional food and cosmetic industries, since its antioxidant potential and vitamin C value were quite high. It can be suggested that the further studies should be conducted in order to spread the consumption of fruits belonging to these species.
Keywords: Rosaceae; correlation; antioxidant activity; vitamin A; vitamin E; vitamin C